Online Dispute Resolution as a Progressive Paradigm for Consumer Dispute Resolution in E-Commerce Transactions - Mochammad Lukman Hakim; I Gede Agus Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The rapid growth of e-commerce has introduced new challenges in consumer protection, particularly regarding dispute resolution mechanisms. Conventional pathways through the courts or the Consumer Dispute Settlement Board (BPSK) have proven inadequate in addressing the complexities of online transactions, which are characterized by cross-border interactions, speed, and relatively small economic values. This situation creates a gap between consumers’ rights to justice and the effectiveness of available dispute resolution mechanisms. This study aims to analyze the limitations of conventional mechanisms in resolving consumer disputes in e-commerce and to explore the role of Online Dispute Resolution (ODR) as a progressive paradigm capable of ensuring legal certainty and consumer protection. The research employs a normative juridical method with a conceptual and legislative approach, examining the compatibility of national regulations with the legal needs of the digital era. The findings reveal that conventional mechanisms are insufficiently adaptive to electronic evidence, hindered by jurisdictional barriers, and inefficient in terms of costs and procedures, thereby reducing consumer access to justice. In contrast, ODR offers a more progressive solution by leveraging technology to provide faster, more affordable, and cross-jurisdictional dispute resolution. The novelty of this research lies in positioning ODR not merely as an alternative mechanism but as a progressive legal paradigm that balances legal certainty with consumer protection. This contributes significantly to the development of a more responsive national legal system in addressing digital challenges.